(untitled) (Journal of the College of Basic Education, 2022)
We can return the process of creating the poetic text to a psychological phenomenon that is inherent to the poet before and during the creative process, because the poet is more interested than others in equating the pleasure of aesthetic sense and making others savor it according to emotional and psychological emotions, so there is a relationship that intertwines between psychology and literature. Theories of psychology are often employed in order to understand human behavior, hence this study came to disclose aspects of this psychological behavior for poets in an era that has many and unique features that differ from what it was in previous times, and the specificity of the state of joy, which is almost a state Accompanying the human being since his creation - as well as poets - we chose to have psychological motivations as the subject of research, and upon our extrapolation of poetic material we decided to take the most important of these motives, which are: holidays, victory in battles, beloved, winery, caliphs.